A history of Filipino civic action groups in Vietnam (1954-1973) - Santos, Kevin Philippe C. (Animo Repository, 2024)
This thesis chronicles the involvement of the Philippines in the Vietnam War focusing on the deployment of Filipino civic action groups in South Vietnam from 1954 to 1973. From the Filipino perspective, the paper discusses and appraises the history and accomplishments of the following civic action groups: Operation Brotherhood (O.B.) and the Freedom Company (F.C.) both formed in 1954, the Philippine Contingent Vietnam to South Vietnam (PHILCONV) that started their activities in 1964, and the Philippine Civic Action Group to the Republic of Vietnam (PHILCAG) that commenced their tour of duty in 1966. During their deployment, these groups rendered medical services, implemented various development projects, and assisted in relevant state-building activities in support of the South Vietnamese government. This thesis also examines the implications of the involvement of Philippines through these civic action groups that were constituted and dispatched in the context of the Cold War. The deployment of these groups was not only fueled by humanitarian concerns for it is a direct consequence of the attempt to confront and contain the spread of communism in Southeast Asia. Keywords: Cold War, Geopolitics, Civic Action, U.S.-Philippine Relationship